Dysphagia as Isolated Manifestation of Jo-1 Associated Myositis? - Labeit, Bendix; Muhle, Paul; Suntrup-Krueger, Sonja; Ahring, Sigrid; Ruck, Tobias; Dziewas, Rainer; Warnecke, Tobias (Frontiers in Neurology, 2019)
Dysphagia can be predominant or sole symptom of myositis. However, diagnostic evaluation is difficult in such cases. Here, we present evidence for dysphagia as sole manifestation of Jo-1 associated myositis. A 77-year-old patient suffering from isolated dysphagia was assessed by flexible endoscopic evaluation of swallowing, videofluoroscopy, high resolution oesophageal manometry, whole body muscle MRI, electroneurographic and electromyographic examination, cerebrospinal fluid analysis, screening for autoantibodies, and body plethysmography. We detected isolated oropharyngeal dysphagia including a decreased pressure of the upper oesophageal sphincter leading to cachexia in an anti-Jo-1 positive patient without any abnormalities in the other diagnostics. Immunosuppressive therapy with cortisone and azathioprine led to long-term improvement of dysphagia. This is the first report of isolated dysphagia as manifestation of Jo-1 associated myositis. Therefore, Jo-1 associated myositis should be considered as a possible differential diagnosis for isolated dysphagia. Typical signs for myositis in instrumental dysphagia assessment are presented.